PERAN KESADARAN WISATA DAN PROMOSI WISATA DALAM MENINGKATAN KUNJUNGAN WISATAWAN KAMPUNG PELANGI DAN SONTOH LAUT (KAPSOL) KECAMATAN ASEMROWO, KELURAHAN TAMBAK SARIOSO - Dwi Ning Anggrani (Universitas Tribhuwana Tunggadewi, 2022)
Tourism is a new model industry that is capable of providing rapid economic growth in income, employment opportunities and activating other sectors in the host country. Specifically, the tourism industry can have a complex regulatory mechanism because it includes regulating the movement of tourists from their country of origin, in tourist destinations to returning to their country of origin. In Asemrowo Subdistrict, Tambak Sarioso Village, Surabaya, namely KAPSOL Tourism, this tour is relatively new and not many people know about this tour. The research method used in writing this article uses qualitative research methods and data collection using interview, observation and documentation techniques. The results of making counseling about